Analisis Perbandingan Pelayanan Jasa Warehousing Pada PT. Big Ocean Transportama, PT. Buana Jaya Cargo Dan PT. Cipta Krida Bahari Di Jakarta Tahun 2023 - Akbar Prakoso (Jurnal Pendidikan Manajemen Transportasi, 2024)
Big Ocean Transportama is a company engaged in the field of Freight forwarder and warehousing services. PT. Big Ocean Transportama realizes the importance of making improvements and increasing warehousing services, namely by comparing warehousing services in companies engaged in the warehousing service business, namely PT. Buana Jaya Cargo and PT. Cipta Krida Bahari as an effort to respond to changes and improvements optimally both internally and externally and to improve the quality of warehousing services. With this description, the author is very interested in studying it in more depth and pouring it into a Journal with the title "COMPARATIVE ANALYSIS OF WAREHOUSING SERVICES AT PT. BIG OCEAN TRANSPORTAMA, PT. BUANA JAYA CARGO AND PT. CIPTA KRIDA BAHARI IN JAKARTA". The problem in this journal is the increasing competition in warehousing services between freight forwarding companies in Jakarta. The purpose of this study is to determine the effective actions / solutions of PT. Big Ocean Transportama in following up on the results of the comparison of warehousing services between freight forwarding companies in Jakarta. The approach used in this study is a quantitative approach, with a proportional stratified random sampling technique to draw or determine the number of samples in the 3 (three) companies as users of their services, which are then analyzed using Benchmarking (Patok Duga). The data used are primary data and secondary data as supporting data obtained from the company. From the results of the benchmarking analysis (patok duga), it is known that the competition in warehousing services at PT. Big Ocean Transportama as the implementer of benchmarking PT. Buana Jaya Cargo and PT. Cipta Krida Bahari as the comparison company have a tendency to improve the quality of warehousing services by forming a research and development team, forming a market team and stricter supervision carried out by PT. Big Ocean Transportama management towards its employees in the warehouse and the addition of loading and unloading equipment in the warehouse.